UPAYA MENINGKATKAN AKTIVITAS BELAJAR MATA PELAJARAN SISTEM REM DENGAN MENGGUNAKAN MODEL PEMBELAJARAN KOOPERATIF TIPE JIGSAW SISWA KELAS XI TEKNIK KENDARAAN RINGAN SMK TAMANSISWA JETIS YOGYAKARTA TAHUN PELAJARAN 2015/2016 - Wisnu Kusuma Wardani; Samidjo Samidjo (Universitas Sarjanawiyata Tamansiswa, 2017)
This study aimed to know the improvement of learning activity of brake system subject by using jigsaw cooperative learning model. The type of this study was a classroom action research. The research subject was the eleventh grade students of vocational school Tamansiswa Jetis Yogyakart consisted of 31 students. The research object was learning activity of brake system subject by using jigsaw cooperative learning model. Data collection technique used observation. The research instrument was the researcher. Data analysis technique used descriptive analysis and qualitative analysis. This result of the study shows that the use of jigsaw cooperative learning model could improve learning activity of brake system subject. The mean score of learning activity in pre cycle was 36/87% in the interval between 21% - 40% in low category, improved in cycle I 46.54% in the interval between 41% - 60% in enough category, and improved in cycle II became 89.86% in the interval between 81% - 100% in very active category